Microenvironment‐induced TIMP2 loss by cancer‐secreted exosomal miR‐4443 promotes liver metastasis of breast cancer. Issue 7 (22nd January 2020) - Wang, Jinyan; Zhang, Qian; Wang, Dandan; Yang, Sujin; Zhou, Siying; Xu, Hanzi; Zhang, Heda; Zhong, Shanliang; Feng, Jifeng
Abstract: We aimed to investigate the role of exosomal miR‐4443 in metastasis of breast cancer (BCa). In vitro wound‐healing assay and transwell invasion assay were used to investigate effect of miR‐4443 on BCa cells. Animal experiments were performed to confirm its effects in vivo. miR‐4443 promotes the metastasis of BCa cells through downregulating tissue inhibitors of metalloproteinase 2 (TIMP2) and upregulating matrix metalloproteinases (MMPs). Highly invasive BCa cells have a higher expression of miR‐4443 in both cells and exosomes. The exosomes derived from highly invasive BCa cells mainly gather in the primary tumor and liver. In vivo, overexpression of miR‐4443 in noninvasive BCa cells induces liver metastasis, accompanied with downregulated TIMP2, and upregulated MMP‐2 in both the primary tumor and liver. When we armed MCF‐10A exosomes with miR‐4443 inhibitors to treat mice bearing high‐miR‐4443 tumors, exosomes accumulated in the primary tumor, and liver following the upregulation of TIMP2 and downregulation of MMP2, and the metastasis was inhibited. Highly invasive BCa cells destroy natural barriers against metastasis by delivering exosomal miR‐4443 to stromal cells of the primary tumor and impairing TIMP2, consequently activating MMP; circulating exosomal miR‐4443 might promote BCa cells lodging in future metastatic sites through the similar mechanisms. Abstract : Highly invasive breast cancer (BCa) cells destroy natural barriers against metastasis by delivering exosomal miR‐4443 to stromal cells of the primary tumor and impairing tissue inhibitors of metalloproteinase 2, consequently activating matrix metalloproteinases; circulating exosomal miR‐4443 might promote BCa cells lodging in future metastatic sites through the similar mechanisms. Exosomes carrying miR‐4443 inhibitors suppresses liver metastasis of BCa.